Role of Peripherally Inserted Central Catheters in Home Parenteral Nutrition: A 5‐Year Prospective Study. Issue 4 (16th August 2012) - Botella‐Carretero, Jose I.; Carrero, Carmen; Guerra, Eva; Valbuena, Beatriz; Arrieta, Francisco; Calañas, Alfonso; Zamarrón, Isabel; Balsa, Jose A.; Vázquez, Clotilde
Abstract : Background : Home parenteral nutrition (HPN) has become a common therapy, with tunneled central venous catheters (CVCs) being preferred for its administration. Peripherally inserted central catheters (PICCs) are not currently recommended for long‐term HPN, although evidence to support this statement is scarce. The authors aimed to evaluate the outcomes of HPN, focusing on CVC‐related complications. Materials and Methods : All patients attended at the authors' center for HPN from 2007–2011 were prospectively included. HPN composition aimed at 20–35 kcal/kg/d, 3–6 g/kg/d of glucose, 1.0 g/kg/d of amino acids, and <1 g/kg/d of lipids. HPN was infused in an intermittent schedule, mostly at night. Catheter‐related bloodstream infections (CRBSIs) were confirmed with positive semi‐quantitative or quantitative culture of the catheter or simultaneous differential blood cultures drawn through the CVC and peripheral vein. Results : Seventy‐two patients received HPN, with 79 implanted CVCs (48 PICCs, 10 Hickman, and 21 ports). Mean catheter‐days were 129.1 for PICCs, 98.5 for Hickman, and 67.7 for ports ( P = .685). When analyzing CRBSIs, ports had 44, Hickman had 20, and PICC had 0 episodes per 1000 catheter‐days ( P = .078). Only PICCs showed less incidence of CRBSIs vs ports ( P = .043). Multivariate logistic regression, correcting by catheter‐days, patients' age and sex, underlying disease, and type of catheter, showed that only catheter‐days ( P = .031) was a predictor for CRBSIs ( P = .007, Nagelkerke R = = 0.246). Conclusion : PICCs are similar in terms of catheter‐related complications to other CVCs for the administration of HPN, especially for oncology patients with HPN lasting <6 months.